Experiences and Perceptions of Trans and Gender Non-Binary People Regarding Their Psychosocial Support Needs: A Systematic Review of the Qualitative Research Evidence - Mc Cann, Edward; Donohue, Grainne (My University, 2021)
People who identify as trans and gender non-binary experience many challenges in their lives and more interest is being paid to their overall health and wellbeing. However, little is known about their experiences and perceptions regarding their distinct psychosocial needs. The aim of this systematic review is to critically evaluate and synthesize the existing research evidence relating to the unique psychological and social experiences of trans people and identify aspects that may help or hinder access to appropriate psychosocial interventions and supports. The PRISMA procedure was utilized. A search of relevant databases from January 2010 to January 2021 was undertaken. Studies were identified that involved trans people, and addressed issues related to their psychosocial needs. The search yielded 954 papers in total. Following the application of rigorous inclusion and exclusion criteria a total of 18 papers were considered suitable for the systematic review. Quality was assessed using the MMAT instrument. Following analysis, four themes were identified: (i) stigma, discrimination and marginalization (ii) trans affirmative experiences (iii) formal and informal supports, and (iv) healthcare access. The policy, education and practice development implications are highlighted and discussed. Future research opportunities have been identified that will add significantly to the body of evidence that may further the development of appropriate health interventions and supports to this population.
PUBLISHED
Special Edition Editor The International Journal of Environmental Research and Public Health is a peer-reviewed open access scientific journal. Impact Factor 3.36
Keywords: Transgender; Mental Health; Psychosocial; Supports; Experiences; Qualitative evidence; Inclusive Society; LGBTQ+; MENTAL-HEALTH; PSYCHOSOCIAL; Psychosocial Interventions; Transgender; non-binary; psychosocial well-being